Significantly Elevated Serum Lipase in Pregnancy with Nausea and Vomiting: Acute Pancreatitis or Hyperemesis Gravidarum? - Amanda Johnson; Bethany Cluskey; Nina Hooshvar; Daphne Tice; Courtney Devin; Elaine Kao; Suhalia Nawabi; Steven Jones; Lihua Zhang; Chi Dola (Hindawi Limited, 2015)
Hyperemesis gravidarum is a severe manifestation of nausea and vomiting of pregnancy and it is associated with weight loss and metabolic abnormalities. It is known that abnormal laboratory values, including mildly elevated serum lipase level, could be associated with hyperemesis gravidarum. However, in this case report details of two women with hyperemesis gravidarum but with significantly elevated serum lipase levels were discussed. These patients presented with severe nausea and vomiting but without abdominal pain. They were found to have severely elevated lipase levels over 1,000 units/liter. In the absence of other findings of pancreatitis, they were treated with conservative measures for hyperemesis gravidarum, with eventual resolution to normal lipase levels. Although significantly elevated lipase level in pregnant patients with nausea and vomiting is a concern for acute pancreatitis, these two cases of significantly elevated serum lipase without other clinical findings of pancreatitis led to this report that serum lipase could be quite elevated in hyperemesis gravidarum and that it might not be an accurate biochemical marker for acute pancreatitis. Imaging studies are thus necessary to establish the diagnosis of acute pancreatitis.